Statistical Analysis by Linear Regression of the Prevalence of Flatfoot in Preschool Children of a Mexican Community - Carlos I. Cabrera-Perez; Juan A. López-Valdez; Horacio Rostro-González; Jatziry S. Cano-Lara; Miroslava Cano-Lara (Ingeniería, 2024)
Context: In Mexico's rural towns, it is essential to generate a culture of studying the prevalence of flat feet in children aged 3 to 5, whose arch is still in development and can be corrected. By means of a computer application, statistical bar graph and correlation studies via linear regression can validate the results obtained regarding the categorization of infants' footprint type, which are acquired through the Hernández Corvo index (HCI), Clarke’s angle protocol (CA), the Staheli index (SI), the Chippaux index (CI), and the body mass index (BMI).